2022
DOI: 10.1021/acsestwater.2c00440
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances (PFASs) in the Fountain Creek Watershed, Colorado Springs, CO, USA: A Yearlong Investigation of PFAS Levels in Water, Soils, and Sediments

Abstract: Per- and polyfluoroalkyl substance (PFAS) contamination of water resources and impact on affected populations in the southern Colorado Springs metro area have been of research interest since initial reports were announced via local news outlets in 2016. In this study, surface water, soils, and sediments were collected monthly for a full year at eight locations within the Fountain Creek Watershed of Colorado Springs, CO, USA. Using a novel quantitative method, levels of nine PFASs were determined via liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Wastewater treatment works contribute substantially more PFOA to the catchment (20.37 kg/year) than has been estimated at the catchment outlet at Westy (14.36 kg/year), indicating substantial potential storage of PFOA in the River Mersey Basin. Sorption of PFOA and PFOS to sediments has been widely reported, , and PFOA sequestration in river channel sediments possibly explains the attenuation of PFOA loads in the River Mersey Basin. However, such large storage volumes in urban river basins are concerning, and these sediments may represent an important secondary nonpoint source of PFOA to river water and biota .…”
Section: Resultsmentioning
confidence: 94%
“…Wastewater treatment works contribute substantially more PFOA to the catchment (20.37 kg/year) than has been estimated at the catchment outlet at Westy (14.36 kg/year), indicating substantial potential storage of PFOA in the River Mersey Basin. Sorption of PFOA and PFOS to sediments has been widely reported, , and PFOA sequestration in river channel sediments possibly explains the attenuation of PFOA loads in the River Mersey Basin. However, such large storage volumes in urban river basins are concerning, and these sediments may represent an important secondary nonpoint source of PFOA to river water and biota .…”
Section: Resultsmentioning
confidence: 94%
“…Aquifer in this region is contaminated by Aqueous Film Forming Foam (AFFF) use at the Air Force Base. Quezada Davalos et al [ 51 ] found that sites near AFFF use have significantly higher PFAS concentrations than distant sites.…”
Section: Resultsmentioning
confidence: 99%
“…The regional hot spots have PFAS manufacturing plants, industrial sites that utilize PFAS, and/or densely populated communities [47][48][49][50][51][52]. For instance, the hotspot in the northeastern US (NY, DE, NJ, PA, and CT) is in a densely populated region with high consumption of household goods containing PFAS, such as detergents, cosmetics, and food packaging [9].…”
Section: Contamination Hot Spotsmentioning
confidence: 99%
“…Per- and polyfluoroalkyl substances (PFAS), which have been used widely in consumer and industrial products, have long-term environmental persistence. In our reported work, we measured PFAS in water, sediment, and soil surveyed at eight locations monthly for a full year within the Fountain Creek Watershed, Colorado Springs, CO, to assess how selected legacy PFAS varied over time and distance [1] . The PFAS concentration data to support that study are included in a Mendeley repository and described here [2] .…”
Section: Objectivementioning
confidence: 99%